2022
DOI: 10.3390/ijerph19063263
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Service Value Tradeoffs: An Ecological Water Replenishment Model for the Jilin Momoge National Nature Reserve, China

Abstract: Wetlands as an important ecosystem type have been damaged in recent years and restoration of wetland ecosystem functions through ecological water replenishment is one of the important ways. The present study involved the construction of a novel ecological water replenishment model for Jilin Momoge National Nature Reserve (JMNNR) using the interval two-stage stochastic programming (ITSP) method. Breaking down traditional economic models that often sacrifice environmental benefits, the model aims to replenish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Irrational human cultivation and urban expansion degrade vegetation, while the implementation of ecological engineering improves it ( He et al., 2021 ). We can see from the results of land use conversion that in the medium term, with over-exploitation by humans, a large number of vegetation NDVI high value areas (swampy wetlands, woodlands and grasslands) were converted to NDVI low value areas (water bodies, unused land and built-up land) in the study area ( Mao et al., 2019 ); in recent years, with the implementation of ecological projects such as returning wetlands to farmland, forests to farmland, grazing to grass, and river and lake linkages ( Huang et al., 2022 ), a large number of vegetation areas with low NDVI values (cropland and unused land) have been transformed into areas with high NDVI values (grassland and woodland) in the study area. Coupled with the gradual stabilization of cropland size in recent years, with high NDVI crops such as rice and soybean, the study area maintains a high and stable vegetation cover ( Geng and Zhou, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Irrational human cultivation and urban expansion degrade vegetation, while the implementation of ecological engineering improves it ( He et al., 2021 ). We can see from the results of land use conversion that in the medium term, with over-exploitation by humans, a large number of vegetation NDVI high value areas (swampy wetlands, woodlands and grasslands) were converted to NDVI low value areas (water bodies, unused land and built-up land) in the study area ( Mao et al., 2019 ); in recent years, with the implementation of ecological projects such as returning wetlands to farmland, forests to farmland, grazing to grass, and river and lake linkages ( Huang et al., 2022 ), a large number of vegetation areas with low NDVI values (cropland and unused land) have been transformed into areas with high NDVI values (grassland and woodland) in the study area. Coupled with the gradual stabilization of cropland size in recent years, with high NDVI crops such as rice and soybean, the study area maintains a high and stable vegetation cover ( Geng and Zhou, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jilin Province, located in northeastern China, has abundant wetland resources [19]. Huang et al [20] conducted a study on the wetland ecosystem service values of 19 different types within Momoer National Nature Reserve in Jilin Province. Yu et al [21] found that the wetlands of Jilin Province could provide approximately CNY 58.328 × 10 9 of the ecosystem service value annually.…”
Section: Introductionmentioning
confidence: 99%